2009
DOI: 10.1007/s11249-009-9493-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Tribological Performance of Novel Mo x W1−x S2 (0 ≤ x ≤ 1) Inorganic Fullerenes

Abstract: Inorganic fullerene-like (IF) MoS 2 and WS 2 nanoparticles were found to be good friction modifiers and anti-wear additives when dispersed in a lubricant. Their tribological performance seems to be related to the structure, size, and shape of these nanomaterials. The present study describes the tribological properties of a new inorganic fullerene IF-Mo x W 1-x S 2 containing both molybdenum and tungsten disulfide under boundary lubrication. Mo x W 1-x S 2 amorphous inorganic fullerene nanostructures were synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…Recently, Tenne and co-workers [7] suggested that an additional rolling process for well-crystallized and round-shaped particles could enhance the lubricating properties of the IF nanoparticles. A recent trend in the synthesis of the fullerenes is to prepare faulted and strained IF nanostructures to facilitate their exfoliation in the tribological contact and thus to optimize the tribological properties of the lubricant [8]. Recently, some metal-doped fullerenes were also prepared [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tenne and co-workers [7] suggested that an additional rolling process for well-crystallized and round-shaped particles could enhance the lubricating properties of the IF nanoparticles. A recent trend in the synthesis of the fullerenes is to prepare faulted and strained IF nanostructures to facilitate their exfoliation in the tribological contact and thus to optimize the tribological properties of the lubricant [8]. Recently, some metal-doped fullerenes were also prepared [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism called as ''drug delivery mechanism'' by the authors is extremely interesting because the lubrication additive is brought directly inside the contact area without any prior chemical reaction, explaining the reason why IF particles are efficient starting from the first cycle of the test and at ambient temperature. Concerning the IF nanoparticles, it has recently been shown that the shape, structure (degree of crystallinity and number of defects) and size of the nanoparticles strongly affect their lubricating performances [12,13]. For example, Tannous et al [12] showed that small and poorly crystallized fullerenes of MoS 2 are much more efficient than the well-crystallized ones.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the IF nanoparticles, it has recently been shown that the shape, structure (degree of crystallinity and number of defects) and size of the nanoparticles strongly affect their lubricating performances [12,13]. For example, Tannous et al [12] showed that small and poorly crystallized fullerenes of MoS 2 are much more efficient than the well-crystallized ones. The author concluded that, with fullerenes exceedingly discontinuous in their layers, exfoliation process could be enhanced by the large number of defects present in the particles.…”
Section: Introductionmentioning
confidence: 99%
“…They were shown to exhibit very good tribological behavior with numerous potential applications, like additives to lubricating fluids [2,3]; as selflubricating coatings [4] and for improving the mechanical behavior of nanocomposites [5,6]. Indeed products based on these new nanomaterials have already been commercialized.…”
Section: Introductionmentioning
confidence: 99%